1996
DOI: 10.1007/bf00604794
|View full text |Cite
|
Sign up to set email alerts
|

MRI in patients with general paresis

Abstract: Few cases of MRI in neurosyphilis have been reported. We examined the value of MRI in patients with general paresis; MRI was performed on four HIV-negative patients with parenchymatous neurosyphilis. It demonstrated frontal and temporal atrophy, subcortical gliosis and, in one patient, increased ferritin in the basal ganglia. The progression of the lesions on MRI correlated well with the neuropsychiatric disturbances. The MRI findings correlated with the well-known neuropathological findings. This combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 14 publications
1
22
0
5
Order By: Relevance
“…We found only one other reported case of a patient with neurosyphilis who had mineral deposition, presumed to be ferritin, in the basal ganglia. 20 Whether mineral deposition in our patient's brain was related to syphilis, was an incidental finding or was due to a second concurrent disorder is unknown. Mineral deposition in the brain has previously been reported in patients with Parkinson disease and other neurodegenerative diseases.…”
Section: Clinical Presentationmentioning
confidence: 88%
See 1 more Smart Citation
“…We found only one other reported case of a patient with neurosyphilis who had mineral deposition, presumed to be ferritin, in the basal ganglia. 20 Whether mineral deposition in our patient's brain was related to syphilis, was an incidental finding or was due to a second concurrent disorder is unknown. Mineral deposition in the brain has previously been reported in patients with Parkinson disease and other neurodegenerative diseases.…”
Section: Clinical Presentationmentioning
confidence: 88%
“…Mineral deposition in the brain has previously been reported in patients with Parkinson disease and other neurodegenerative diseases. 20 Although there have been a few reported cases of neurosyphilis manifesting with parkinsonism, the incidence is thought to have declined in recent years and remains rare. 13 Because the parkinsonian features in our first patient did not abate or reverse after treatment with penicillin and persisted unchanged over the 4 years after all neuroleptics were stopped, the relative contribution of neurosyphilis and neuroleptics to his parkinsonian features remains unclear.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…However, in a review of the current literature, limbic lesions have not been described in syphilitic meningovasculitis (1,3,4). On the other hand, in genera] paresis, cerebral cortical atrophy and white matter changes have been emphasized (6,7). In only one of 3 cases described b> Zifko et al (7), high signal lesions and marked atrophy were observed in both hippocampi at the chronic stage.…”
Section: Discussionmentioning
confidence: 99%
“…При этом на КТ/МРТ определяется кортикальная цереб-ральная и церебеллярная атрофия с множественными очага-ми, при SPECT -гипоперфузия во фронто-темпоральных областях [61,62]. При нейровизуализационном исследова-нии у пациентов с прогрессивным параличом выявляется церебральная атрофия, а у больных с менинговаскулярным сифилисом, протекающим с картиной мультиинфарктной деменции, -множественные постинсультные очаги [63][64][65][66][67]. Описано небольшое количество случаев, при которых ней-ровизуализационная картина напоминала БА.…”
unclassified
“…В 1 из 4 случа-ев, представленных U. Zifko и соавт. [63], при МРТ головно-го мозга выявлены двусторонняя атрофия и глиоз гиппокам-пов. Другой пациент [68] имел когнитивные и поведенче-ские симптомы, а при МРТ головного мозга наблюдалась ат-рофия медиальных височных областей, которая соответст-вовала ранним изменениям при БА.…”
unclassified